Market Valuation of Indonesian Listed Firms: The Impact of Economic Growth, Profitability, Political Connections, and Firm Size - Maudi Intan Nadila; Perdana Wahyu Santosa (Taxation and Public Finance, 2026)
This study examines the influence of economic, financial, and political factors on firm value among non-financial companies listed in the LQ45 Index of the Indonesia Stock Exchange during 2019–2023. The research addresses inconsistent findings regarding the effects of macroeconomic conditions, profitability, political connections, and firm characteristics on firm value in emerging markets. It also incorporates an Islamic perspective by evaluating whether these determinants align with the principles of transparency, accountability, and value creation emphasized in Islamic business ethics. Using a quantitative approach and panel data regression analysis, this study analyzes secondary data from non-financial LQ45 companies. Firm value is assessed in relation to Gross Domestic Product (GDP), Return on Equity (ROE), political connections, and firm size. The results show that GDP and political connections do not significantly affect firm value. Conversely, ROE has a positive and significant effect, indicating that greater profitability enhances market valuation. Firm size has a significant negative effect on firm value, suggesting that larger firms may encounter efficiency challenges. These findings imply that managers should focus on improving profitability and operational efficiency. From an Islamic perspective, the results highlight the importance of accountability and performance-based value creation.